Ragam Gaya Belajar Siswa Berprestasi di Pesantren Nurul Madani Salatiga - Atika Muallifah (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2024)
This research discusses the learning styles of high-achieving students at the Nurul Madani Islamic Boarding School in Salatiga. This study aims to determine the learning styles of high-achieving students, to understand how students overcome limited time for studying, and to identify the factors that support the learning process of high-achieving students at the Nurul Madani Islamic Boarding School in Salatiga. This study is qualitative, with the research subjects consisting of three outstanding students from the Nurul Madani Islamic Boarding School in Salatiga. Data was collected through interviews, observations, and documentation, which were then analyzed descriptively. The results show that the learning styles of the three high-achieving students differ, with one using an auditory learning style, another using a kinesthetic learning style, and the third using a visual learning style. To make the most of their limited time, the high-achieving students at Nurul Madani Salatiga manage their time efficiently and maximize their free time. Two factors support their achievements: internal factors, such as self-motivation, and external factors, including support and motivation from their parents and the boarding school environment. Most students are supported by the Islamic boarding school, which provides facilities to help them develop their potential.